In vivo Fitness of Acinetobacter baumannii Strains in Murine Infection Is Associated with International Lineage II-rep-2 and International Lineage III Clones Showing High Case Fatality Rates in Human Infections - Amir Nutman; Jonathan Lellouche; Ziv Lifshitz; Rivka Glick; Yehuda Carmeli (Microorganisms, 2020)
We previously reported that the 14-day case fatality rate (CFR) in patients with carbapenem-resistant Acinetobacter baumannii (CRAB) bacteremia varied between infecting clones. Here, we evaluated the in vitro and in vivo fitness of CRAB blood isolates belonging to clones with low CFR (< 32% 14-day mortality) and high CFR (65% 14-day mortality). Fitness was measured in vitro using a growth curve assay and in vivo using murine thigh muscle and septicemia models of infection. Our sample included 38 CRAB isolates belonging to two clones with low CFR (international lineage (IL)-II-rep-1, n = 13 and IL-79, n = 6) and two clones with high CFR (IL-III, n = 9 and IL-II-rep-2, n = 10). In in vitro growth curves, mean lag time, generation time and maximal growth varied between clones but could not discriminate between the high and low CFR clones. In the in vivo models, bacterial burdens were higher in mice infected with high CFR clones than in those infected with low CFR clones: in thigh muscle, 8.78 ± 0.25 vs. 7.53 ± 0.25 log10CFU/g, p < 0.001; in infected spleen, 5.53 ± 0.38 vs. 3.71 ± 0.35 log10CFU/g, p < 0.001. The thigh muscle and septicemia model results were closely correlated (r = 0.93, p < 0.01). These results suggest that in vivo but not in vitro fitness is associated with high CFR clones.